2017
DOI: 10.1096/fj.201601288rrr
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐specific caveolin‐1 overexpression improves motor function and preserves memory in mice subjected to brain trauma

Abstract: Studies and demonstrate that membrane/lipid rafts and caveolin (Cav) organize progrowth receptors, and, when overexpressed specifically in neurons, Cav-1 augments neuronal signaling and growth and improves cognitive function in adult and aged mice; however, whether neuronal Cav-1 overexpression can preserve motor and cognitive function in the brain trauma setting is unknown. Here, we generated a neuron-targeted Cav-1-overexpressing transgenic (Tg) mouse [synapsin-driven Cav-1 (SynCav1 Tg)] and subjected it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…Previous work from our group demonstrated, at minimum, 12 mo of gene expression using a 1-time intraparenchymal dose of adeno-associated virus serotype 9 (AAV9)-SynCav1 (19). Intrathecal delivery, direct spinal cord, and brain injections have all demonstrated safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work from our group demonstrated, at minimum, 12 mo of gene expression using a 1-time intraparenchymal dose of adeno-associated virus serotype 9 (AAV9)-SynCav1 (19). Intrathecal delivery, direct spinal cord, and brain injections have all demonstrated safety.…”
Section: Discussionmentioning
confidence: 99%
“…These primers were used to detect a product size of 800 and 600 base pair (bp) for mouse and human SOD1, respectively. SynCav1 transgenic mice were generated in C57BL/6 background through the UCSD mouse transgenic core (19). Full-length Cav-1 cDNA (537 bp) was cloned into a vector containing the human neuron-specific synapsin promoter (495 bp) (20) and termed SynCav1 as previously described in refs.…”
Section: Hsod1 G93a Mouse Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a neuroprotective role, additional studies have shown that Cav-1 promotes neuronal and synaptic plasticity and improves neurobehavior Egawa et al, 2017a,b;Mandyam et al, 2017). Using a neuronspecific synapsin promoter to express Cav-1 (termed SynCav1) specifically in neurons, Cav-1 overexpression enhanced cellular cholesterol accumulation and raft formation, augmented receptor-mediated cAMP production, functional NMDAR (P-Src, P-CaMKII, P-ERK1/2) and TrkB signaling (P-TrkB, P-Akt), dendritic growth and arborization in vitro and in vivo (Mandyam et al, 2017) and prevented hippocampal-dependent learning and memory loss and improved motor function in a murine model of traumatic brain injury (Egawa et al, 2017a). Further work from our group showed that when delivered to the hippocampus in vivo, AAV9-SynCav1 increased hippocampal neuroplasticity, improved fear learning and memory in adult and aged mice (Mandyam et al, 2017), and promoted ultrastructural and functional indicators of synaptic plasticity (Egawa et al, 2017b), suggesting that Cav-1 and raft microdomains alter aspects of synapse biology necessary for functional neuronal and synaptic plasticity.…”
Section: Brainmentioning
confidence: 99%
“…Enhancing MLR-localization of NTRs may augment prosurvival and pro-growth signaling, enhance structural and functional neuroplasticity, or even increase the efficacy of exogenous or already present endogenous growth factors, which in turn may restore cognitive function in AD. One such gene therapy candidate is caveolin-1 (Cav-1), a MLR scaffolding protein that organizes NTRs (Trk) and neurotransmitter receptor signaling complexes in MLRs [12][13][14]. Both pre-clinical and clinical findings revealed that Cav-1 and Cav-1 associated signaling complexes (NTRs and neurotransmitter receptors) were decreased in degenerating neurons in AD, chronic traumatic encephalopathy (CTE), and amyotrophic lateral sclerosis (ALS) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%